Pengaruh Harga dan Promosi Terhadap Keputusan Pembelian Helm Merek GM Pada Mahasiswa/i Sekolah Tinggi Ilmu Ekonomi Haji Agus Salim Bukittinggi - Hariman Syaleh; Rohimah Nur Nasution (Training & Research Institute - Jeramba Ilmu Sukses, 2020)
This research is motivated by many types and brands of helmets offered to consumers in the market. So that each helmet company must create a strategy to maintain and achieve a higher market share. The problem in this study is